Traffic modelling of the video-on-demand service through NS-3 (2017)
The principal characteristic of the video on demand service through video streaming technology is the consumption of large bandwidths, which is why network planners must consider the service when dimensioning said networks. To achieve this goal, one of the tools is traffic engineering and its associated models. Thus, this article presents a traffic model based on simulation through discrete events and developed through the open code software and of research on networks, denominated ns-3. This work describes the abstractions of network elements and the construction process of different evaluation scenarios, independent of the characteristics of the service sought to be analyzed, and the collection and graphic visualization de statistics. Finally, the work presents the analyses of the performance parameters that permit obtaining the minimum network characteristics to support the service.